A Bibliometric Analysis of Knowledge Production in Nepal: Trends, Gaps, and Pathways to Inclusive Scholarship in the International Research Journal of MMC - Neupane, Dasarath; Aryal, Uttam (International Research Journal of MMC, 2026)
Background: Multidisciplinary academic journals are an important element in Nepal in shaping the scholarly discourse and informing national development priorities. As the national agenda develops a roadmap with focus on an inclusive and resilient society, the need arises for an examination of whether the country's own knowledge production gives expression to this commitment towards equity and diversity.Objectives: The bibliometric study was carried out to map the research trends, thematic focus, collaboration patterns, and gaps of IJRMMC for assessing its contributions to inclusive and resilient scholarship in Nepal.Methods: Bibliometric analysis was done using metadata of all the publications from IJRMMC indexed in Lens.org. Data were analyzed using VOSviewer for co-authorship and keyword co-occurrence network visualization, and Wordsift.org for lexical analysis of titles and abstracts.Findings: Empirical foci on education, public health, and community-based studies suggest a high level of interest, though COVID-19 related research further gains prominence. However, large gaps remain: the so-called issues of lowest priority include caste, ethnicity, Madhesi issues, disability, and climate justice. Geographical clustering of research in urban centres and author collaboration networks are marked by limited cross-cluster or inter-discipline linkages.Conclusion: This leads to the clear conclusion that, even though the journal's output is robust in some sectors, it is by no means totally in line with today's broader sociological imperative for inclusive knowledge production. The gaps noted indicate a trend towards homogenized scholarship that may serve to unconsciously reinforce well-entrenched social and spatial inequalities.Implementation: To fill these gaps, the journal and other similar platforms could introduce special issues targeting this, revise submission guidelines to include encouragement for such intersectional analyses, and offer incentives toward collaborative and geographically diverse research. Policies at the academic institutional level should be directed at supporting the production of decentralized knowledge and encouraging collaboration that bridges disciplines and regions.